Osteogenic shift in the adipose-derived stem cells of Acomys cahirinus is linked to impaired adipose tissue self-renewal - M. Boldyreva; M. Boldyreva; E. Zubkova; E. Trubkina; E. Trubkina; M. Agareva; M. Agareva; S. Michurina; N. Alekseeva; I. Beloglazova; E. Ratner; Ye Parfyonova; et al. (Frontiers in Cell and Developmental Biology)
BackgroundIn recent years, there has been a significant increase in interest in Acomys cahirinus due to their unique regenerative properties and specific metabolism. We propose that Acomys sp. adipose-derived stem cells (ADSC) may have unique properties allowing them to adapt to caloric overload and prevent severe metabolic abnormalities. ADSC characterization from Acomys cahirinus may reveal novel pro-regenerative targets and provide insight into mechanisms enabling the maintenance of metabolic health during obesity.MethodsADSCs were isolated from the subcutaneous fat depots of Acomys cahirinus and Mus musculus, which was used as a classic lab animal rodent model. The mesenchymal phenotype of ADSC was confirmed by surface markers expression and differentiation ability. Proliferation and migration of ADSC were assessed by metabolic tests and microscopy. Osteogenesis and adipogenesis were evaluated by specific staining and RT PCR gene expression analysis. Subcutaneous adipose tissue was characterized by histology and Western blotting.ResultsAcomys cahirinus ADSC exhibited classic mesenchymal phenotype. Proliferation and wound healing were more active in Acomys cahirinus ADSC. These ADSC demonstrated enhanced osteogenesis and suppressed adipogenesis. Acomys cahirinus has larger adipose tissue depots than Mus musculus and lower blood glucose level. Acomys cahirinus adipose tissue is distinguished by lowered proliferation, enlarged adipocytes and suppressed adipose tissue triglyceride lipase (ATGL) expression.ConclusionWe conclude that Acomys cahirinus ADSC have high regenerative potential. Nevertheless, the augmented osteogenic capacity of Acomys cahirinus ADSC can be related with a limited ADSC participation in adipose tissue self-renewal. The reduction in ATGL expression observed in Acomys cahirinus adipose tissue may serve as a protective mechanism in the face of excessive adipose tissue accumulation.